Salivary ACE2 and TMPRSS2 link to periodontal status and metabolic parameters - Dan Zhao; Tianfan Cheng; Mohamad Koohi‐Moghadam; Mei‐Zhen Wu; Shuk Yin Yu; Xun Ding; George Pelekos; Kai Hang Yiu; Lijian Jin (Clinical and Translational Discovery, 2022)
Abstract Background Periodontitis links extensively to various non‐communicable diseases such as diabetes and cardiovascular disease and most recently COVID‐19 complications. Two important proteins in humans, ACE2 and TMPRSS2, have been associated with various health problems and coronavirus infection. This study was to investigate the soluble ACE2 and TMPRSS2 in saliva and serum as well as their association with periodontal status and systemic conditions. Methods The demographic background, lifestyles, full‐mouth periodontal status and medical parameters in 139 subjects were examined and recorded. Saliva and serum samples were collected for determining the levels of ACE2, TMPRSS2 and MMP8. Findings The salivary levels of ACE2 increased with the severity and complexity of periodontitis and correlated positively with alveolar bone loss and salivary MMP8 as an inflammatory biomarker. While, the salivary levels of TMPRSS2 were negatively correlated with body mass index (BMI), cholesterol/high‐density lipoprotein (HDL) ratio, low‐density lipoprotein (LDL), salivary MMP8 and number of remaining teeth. No inter‐correlation existed among ACE2 and TMPRSS2 levels in both saliva and serum. Conclusions The present study demonstrated the disparate correlation of the soluble ACE2 and TMPRSS2 with periodontal and systemic parameters. Salivary ACE2 could differentiate periodontal health and severe periodontitis, while salivary TMPRSS2 prominently linked to the metabolic parameters of obesity and cardiovascular disease. Our findings imply the potential application of the biofluidic soluble form of SARS‐CoV‐2 entry proteins in assessing oral or systemic conditions and delivering appropriate healthcare.